Antiepileptic and anti-inflammatory effects of Lippia multiflora moldenke (Verbenaceae) in mice model of chronic temporal lobe epilepsy induced by pilocarpine - Joseph Ngaibi; Bigued; Antoine Kavaye Kandeda; Yvette Nguezeye; Tchang Alkali Wangbara; Lamido Gaoudji; Germain Sotoing Taiwe; Elisabeth Ngo Bum (Heliyon)
Lippia multiflora Moldenke (Verbenaceae) is an aromatic plant used as a popular medicine with antidepressant, antispasmodic, antifungal, anti-inflammatory, and antioxidant properties. In this study, we explored the effects of L. multiflora in mice chronic model of temporal lobe epilepsy induced by pilocarpine and kindled with pentylenetetrazol. Mice were divided into 7 groups of 10 animals, and received a single dose of pilocarpine (360 mg/kg, i.p.), 20 min after the administration of N-methyl-scopolamine (1 mg/kg, i.p). Thirty days after the induction of status epilepticus, animals were daily treated for 60 days with distilled water (10 mL/kg, per os) for the negative control group, extract (23.07, 57.69, 115.39 and 230.78 mg/kg, per os) for the test groups, and sodium valproate (300 mg/kg, i.p) for the positive control group. On every 10th day, animals were injected with a sub-convulsive dose of pentylenetetrazol (15 mg/kg, i.p) 1 h after the administration of the various treatments to assess the susceptibility of animals to seizures. At the end of behavioural tests, animals were sacrificed and the level of inflammatory cytokines was assessed in the hippocampus. The plant extract reduced (p < 0.001) the occurrence of seizures and the number of spontaneous recurrent seizures induced by pilocarpine in mice. It ameliorated the levels of inflammatory cytokines (TNF-α, INF- γ, IL-1β, IL-6, and IL-10) in the hippocampus. The in vitro studies show that L. multiflora have a high amount of total phenolic content, flavonoids and tannins and also have some good antioxidant properties. These results suggest that L. multiflora aqueous extracts has the potential to be a promising complementary and alternative medicine for the treatment of epilepsy, due to its antiepileptic, anti-inflammatory and antioxidant effects.